2007
DOI: 10.1091/mbc.e06-10-0975
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Microglia Acidifies Lysosomes and Leads to Degradation of Alzheimer Amyloid Fibrils

Abstract: Microglia are the main immune cells of the brain, and under some circumstances they can play an important role in removal of fibrillar Alzheimer amyloid ␤ peptide (fA␤). Primary mouse microglia can internalize fA␤, but they do not degrade it efficiently. We compared the level of lysosomal proteases in microglia and J774 macrophages, which can degrade fA␤ efficiently, and we found that microglia actually contain higher levels of many lysosomal proteases than macrophages. However, the microglial lysosomes are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
227
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(236 citation statements)
references
References 42 publications
(52 reference statements)
5
227
1
3
Order By: Relevance
“…Interestingly, it was recently reported (based on genetic perturbations) that microglial PGRN limits amyloid plaque deposition in a mouse AD model (31). However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Interestingly, it was recently reported (based on genetic perturbations) that microglial PGRN limits amyloid plaque deposition in a mouse AD model (31). However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66).…”
Section: Discussioncontrasting
confidence: 47%
“…Similar structures were described in seminal electron-microscopy studies of human AD brain tissue (9). Given the central role for lysosomes as sites of macromolecule degradation, combined with roles for microglia in amyloid plaque phagocytosis and clearance (22,23), we next investigated the contributions of microglia to these plaque-associated lysosome accumulations.…”
Section: Ultrastructural Analysis Of Organelle Accumulation Surroundingmentioning
confidence: 99%
“…The A␤ levels are determined by the balance between its production and degradation/clearance, and an attenuated A␤ catabolism is suggested to cause A␤ accumulation in aging brains (14). Previous studies have shown that astrocytes and microglia directly take up and degrade A␤42 (15,16) and that A␤ degradation occurs in late endosomal-lysosomal compartments (17,18). These lines of evidence, together with the finding that LPL mediates the cellular uptake of lipoproteins (1,2), led us to carry out experiments to determine whether LPL interacts with A␤ to promote A␤ cellular uptake and degradation in astrocytes.…”
mentioning
confidence: 98%
“…Finally, a new drug potentially useful in the treatment of both diseases is ademetionine, an antidepressant (depression is one of the main psychiatric symptoms of AD) that appears to reduce the aggregation of β-amyloid fibrils [183,184] and shows neuroprotective effects on RGCs [185,186].…”
Section: Glutamate Modulationmentioning
confidence: 99%